Access to Norwegian healthcare system - challenges for sub-Saharan African immigrants - Vivian N. Mbanya; Laura Terragni; Abdi A. Gele; Esperanza Diaz; Bernadette N. Kumar (BMC, 2019)
Abstract Background Immigrants face barriers in accessing healthcare services in high-income countries. Inequalities in health and access to healthcare services among immigrants have been previously investigated. However, little is known on the sub-Saharan African immigrants' (SSA) access to the Norwegian healthcare system. Methods The study had a qualitative research design. We used the snowball technique to recruit participants from networks including faith-based organizations and cultural groups. Forty-seven qualitative in-depth interview and two focus group discussions with immigrants from sub-Saharan African were conducted from October 2017 to July 2018 in Oslo and its environs. Interviews were conducted in Norwegian, English or French, audio-recorded and transcribed verbatim into English. The analysis was based on a thematic approach, using NVivo software. Interview data were analyzed searching for themes and sub-themes that emerged inductively from the interviews. Results Our findings reveal barriers in two main categories when accessing the Norwegian healthcare services. The first category includes difficulties before accessing the healthcare system (information access, preference for doctors with an immigrant background, financial barriers, long waiting time and family and job responsibility). The second category includes difficulties experienced within the system (comprehension/expression and language, the black elephant in the room and dissatisfaction with healthcare providers). Conclusion Healthcare is not equally accessible to all Norwegian residents. This ultimately leads to avoidance of the healthcare system by those most in need. Lack of seeking healthcare services by immigrants from Sub Saharan Africa may have significant implications for the long-term health of this group of immigrants. Therefore measures to address the issues raised should be prioritized and further examined.